A Comparative Study Of The Teachings Of The Qur’an And The Analects On Man And Nature - Yang, Jie (2017)
Man is surrounded by nature and can hardly survive out of it. He is always being reminded of its influence on him through all the different natural elements. Human development have progressed or deteriorated as a result of the environmental conditions and geography of the earth